(untitled) (Research, Society and Development, 2020)
This study evaluated the molluscicidal activity of essential oils (EOs) of Syzygium cumini L. and Hymenaea courbaril L. Hydrodistillation was used to extract the EOs. The chemical characterization was performed by Gas Chromatography coupled to mass spectrometry. The bioassay of Artemia salina Leach was used for the toxicity test. The molluscicidal assay tested concentrations of 10-80 mg L-1 of the EOs against Biomphalaria glabrata. The major constituent of The EO of S. cumini was isokaryophyllene and H. courbaril the Germacreno-D. The toxicity assay classified The EOs as nontoxic with LC50 412.10 mg L-1 for S. cumini and LC50 354.80 mg L-1 for H. courbaril. The molluscicidal assay purchased LC50 44.76/ LC90 77.20 for S. cumini and LC50 37.34 mg L-1/ LC90 73.24 mg L-1 for H. courbaril. The results showed that both EOs can be used as natural molluscicides in combating the snail Biomphalaria glabrata.